2010
DOI: 10.1371/journal.ppat.1001047
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Lysin Mediates the Binding of Streptococcus mitis to Human Platelets through Interaction with Fibrinogen

Abstract: The binding of bacteria to human platelets is a likely central mechanism in the pathogenesis of infective endocarditis. We have previously found that platelet binding by Streptococcus mitis SF100 is mediated by surface components encoded by a lysogenic bacteriophage, SM1. We now demonstrate that SM1-encoded lysin contributes to platelet binding via its direct interaction with fibrinogen. Far Western blotting of platelets revealed that fibrinogen was the major membrane-associated protein bound by lysin. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 53 publications
(76 reference statements)
1
70
0
Order By: Relevance
“…Also seen were the expected diversity of lysins (Seo et al 2010), holins (Wang et al 2000), bacteriocins (Dawid et al 2007), restriction/modification systems (Kobayashi 2001), and virulence factors (O'Brien et al 1984;Lainhart et al 2009;Campos et al 2010).…”
Section: Genome Research 1621mentioning
confidence: 98%
“…Also seen were the expected diversity of lysins (Seo et al 2010), holins (Wang et al 2000), bacteriocins (Dawid et al 2007), restriction/modification systems (Kobayashi 2001), and virulence factors (O'Brien et al 1984;Lainhart et al 2009;Campos et al 2010).…”
Section: Genome Research 1621mentioning
confidence: 98%
“…It is likely that the initial adhesion events occur independently of platelet activation and thus make suitable targets in the prevention of IE. In contrast, as the ability to induce platelet aggregation (activation) in vitro contributes to the virulence and persistence of the organism in infective endocarditis animal models [87,95], the pathways of platelet aggregation are targets of future IE therapies. Consistent with this, a recent study has examined the effect of antiplatelet drug Reopro (abciximab) in the treatment of sepsis in mice [113] and the use of cyclooxygenase inhibitors, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…When investigated further, the phage lysin was found to bind fibrinogen via the D fragment of the Aα and Bβ chains, and in doing so can mediate an indirect interaction with human platelets through αIIbβ3 [87]. Like PblA and PblB, it is also a choline binding protein but with homology to the choline binding domain of pneumococcal LytA [87]. The fibrinogen interactive domain was localized to amino acids 102-198 [88] and when this polypeptide was preincubated with platelets and S. mitis SF100, it significantly extended the lag time to aggregation.…”
Section: Phage Encoded Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…S. mitis strains lacking the expression of PblA and PblB demonstrated significant decrease in platelet binding invitro as well as marked reduction in virulence in an animal model of infective endocarditis (Bensing et al, 2001b;Mitchell et al, 2007). More recent studies have demonstrated that S. mitis surface bound lysin can bind both free and platelet bound fibrinogen, through its interaction with the Aa and Bb chains of fibrinogen (Seo et al, 2010). Once S. mitis has bound fibrinogen this in turn can bind to the platelet fibrinogen receptor, GPIIbIIIa, initiating thrombus formation.…”
Section: Platelet-bacterial Interactions: the Streptococcusmentioning
confidence: 99%